A Brief Review of Analytical Methods for the Estimation of Allopurinol in Pharmaceutical Formulation and Biological Matrices - Hemraj Sharma; Hari Prasad Sapkota; Nim Bahadur Dangi (International Journal of Analytical Chemistry)
This review article represents the collection and discussion of various analytical methods available in the literature for the determination of allopurinol (ALLP) in pharmaceutical and biological samples consisting of HPLC, UV-visible method, near-IR spectroscopy, spectrofluorometry, capillary electrophoresis, polarography, voltammetry, and hyphenated techniques such as LC-MS, LC-MS/MS, UPLC-MS/MS, and GC-MS. The anticipated review provides details about the comparative utilization of various analytical techniques for the determination of ALLP. The present review article can be effectively explored to conduct future analytical investigation for the estimation of ALLP.